20th-Century Marseilles. From Italian Predominance to North African Diversity - (:unkn) unknown (My University, 1995)
Marseilles has always been a city of migrations. But until the late 19th century, this mainly concerned Italians moving to Marseilles from neighboring areas. The arrival of workers from the colonies, especially the North African ones, is an example of the « imperial retreat » which began in the first half of the 20th century. This migration, dominated by Algerians, is important not only for the whole of the French economy, but also for the economies of the Maghreb, which it supports fïnancially. The primordial place the North African minorities have recently taken in the city is, nevertheless, singularly complex. It is characterized both by a high rate of joblessness among unskilled workers and by the birth of a trading system with international ramifications.
Keywords: African Research